STUDY OF ANTIOXIDANT PROPERTIES AND ACTIVITY OF TWO RICE BRAN EXTRACTS FROM LOCAL CULTIVARS IN INDIA - S. NAKTODE, KISHOR (The Bioscan, 2023)
The rice bran varieties native to India, Oryza sativa L. CV. Mohara (RB-1) and Oryza sativa L. CV. Kedarnath (RB2), which are extensively cultivated, exhibit a noteworthy abundance of antioxidant components. Employing spectrophotometric techniques, the antioxidant attributes, including total phenolic content, 1, 1-diphenyl-2picryl-hydrazil (DPPH) scavenging, and 2, 22 - azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) radicalscavenging, of rice bran extracts were assessed. The present study revealed that the isopropanolic extracts from rice bran yielded promising outcomes, with EC-50 values in the DPPH and ABTS assays for RB-1 measuring 0.64 ± 0.06 and 0.63 ± 0.05 mg/mL, respectively, and for RB-2, 0.69 ± 0.03 and 0.55 ± 0.03 mg/mL, respectively. The highest levels of total phenolic content within rice bran extracts were detected in RB-1, specifically 4.34 ± 0.062 mg gallic acid eq/g. As a result, it is conceivable that isopropanolic extracts derived from these rice bran varieties hold potential utility as natural antioxidants